Unexpected Mobility Variation among Individual Secretory Vesicles Produces an Apparent Refractory Neuropeptide Pool - Ng, Yuen-Keng (Biophysical Society, 2003)
Most stored neuropeptide cannot be released from nerve terminals suggesting the existence of a refractory pool of dense core vesicles (DCVs). Past fluorescence photobleaching recovery, single particle tracking and release experiments suggested that the refractory neuropeptide pool corresponds to a distinct immobile fraction of cytoplasmic DCVs. However, tracking of hundreds of individual green fluorescent protein-labeled neuropeptidergic vesicles by wide-field or evanescent-wave microscopy shows that a separate immobile fraction is not evident. Instead, the DCV diffusion coefficient (D) distribution is unusually broad and asymmetric. Furthermore, the distribution shifts with a release facilitator. This unexpected variation, which could reflect heterogeneity among vesicles or in their medium, is shown to generate the appearance of a regulated refractory neuropeptide pool.